A Study on Social Control in Formation of Accounting Information System Development: A Case Study of Postgraduate Students in Universiti Utara Malaysia - Oulowa, Ahlam Abdullah Ibrahim (2011)
An important and continuing area of behavioral accounting research has examined the relation between the effects of social factors on the accounting system and its development. This research has explicitly recognized that the importance of social control in formatting the development of accounting information system is determined not only by irrelevant products of information but also by the user complain of difficulty to use it that refers to the gap between the rules and practice. Accounting Information System (AIS) is a complex and fast growing area particularly in the field where the social norms are involved. Recent studies have found social influence to be positively related to information system development. The study was conducted on 100 postgraduate students studying in UUM. The results of the study indicated that social norms have no effect on AIS development. The implication of the study is a suggestion that developers of accounting system should take into their account the social factors more involved in the development of the system. Another potential area of study is to compare the AIS programs and Post AIS graduates of different universities to see if there are differences. The results of this study may help universities to develop better AIS programs.